The Compatibility between Philosophy Basis of ‘English in Mind’ Textbook and Curriculum 2013 - Ida Megawati; Darmiyati Zuchdy (Universitas Hamzanwadi, 2020)
A textbook should reflect the curriculum being applied. The compability of the philosophical foundation between curriculum and textbook is needed to achieve educational goals. This study aims to find the philosophical foundation of the English in Mind Students' Book and the compability of the philosophical foundation between the curriculum and the textbook. This study is an inferential content analysis. The object is the English in Mind Students' Book. The procedure is the data making; physical and referential units, sampling; six chapters, data recording, data reduction, and withdrawal of inference. This study used semantic validity and test-retest reliability. This study used analytic constructs as a reference for the meaning of data to be analyzed using conceptual domain analysis techniques. Based on data analysis, there are six philosophies namely philosophy of perennialism, progressivism, essentialism, existentialism, humanism, and social reconstruction in the English in Mind Students' book while there are six philosophies namely essentialism, humanism, social reconstruction, idealism, progressivism, and perennialism in curriculum 2013. There is a difference in philosophical foundation but this does not reduce the purpose and content of curriculum and textbooks. Both emphasize critical thinking skills, problem solving, communication and collaboration, creative and innovative and character development for students.